Mongolia Trade and Transport Facilitation Action Plan - World Bank (Washington, DC, 2013)
This report develops and expand on the Trade Facilitation and Logistics Development Strategy Report, published in December 2006. This report employs a supply chain perspective which focuses on the trade and transportation needs of the products and supply chains assessed. These specific needs are then compared with the trade facilitation services available, the gaps between these and the needs identified, recommendations made for closing the gaps. Three export and three import products/product groups have been chosen for analysis, for the highest export growthpotential. Given the recent dramatic decline in the market price of minerals and the drop in demand for them, diversification of Mongolia's economy and international trade has assumed renewed importance. In this review we have combined attention to traditional exports as support for diversification of trade, while not ignoring the export of minerals and import of mining equipment as these will continue to be important.